Dataset of sediment analyses (pH, electrical conductivity, magnetic susceptibility, loss on ignition, and X-ray fluorescence) from the Deliktaş catchment in the Pergamon micro-region, western Türkiye - Xun Yang; Fabian Becker; Moritz Nykamp; Brigitta Schütt (PANGAEA, 2023)
The data support the interpretation of varying sediment facies and the reconstruction of the Holocene alluvial fan dynamics on the Deliktaş catchment in the micro-region of an ancient city Pergamon, west Turkey (Yang et al., under review). This dataset of sediment analyses was collected through the field work in the Deliktaş alluvial fan and laboratory measurements in the Bergama excavation house on October 2021. It comprises the geochemical and element composition of the sediment samples from five sediment sequences (Del-2, Del-3, Del-4, Del-5, and Del-6). Bulk geochemical sediment analyses include pH and electrical conductivity (EC) by a TDS/EC/pH/TEMP meter, mass magnetic susceptibility of low frequency (XLF) by Bartington magnetic susceptibility system (MS2B or MS3 sensor), and loss on ignition on 550 °C (LOI550) by temperature-controlled furnace. In order to test the suitability of the LOI550 for estimating organic matter, we measured the samples of two profiles (AD29 and AD30) from the western lower Bakırçay plain in the sedimentary laboratory in Freie Universität Berlin. The element composition was analyzed using the p-XRF device. The data of sediment samples were recorded in Excel, calculated and illustrated in R software (R Core Team, 2021) and imported into Inkscape software. The sample extquotesingles depth is simplified by its middle depth. For the XLF measurement, the confidence intervals of the median are estimated by simple quantile bootstrapping (B = 1,000) in R. The sediment parameters of each sediment unit in this study are summarized in median and median absolute deviation (MAD, in brackets) which was calculated in R and they are descripted into 5 classes based on Yang et al. (2023).